Frequency Distribution Of The Incidence Of Postpartum Blues In Adolescent Mothers After Childbirth - illustri, illustri (Jurnal EduHealth, 2023)
Postpartum mothers are vulnerable to various mental disorders, one of which is postpartum blues. Postpartum blues arise when a person does not successfully adjust to changes in life patterns due to pregnancy, labor and postpartum process. Mothers with young age who are still not ready to be morally responsible often face mental shocks due to still having unstable mental attitudes and immature in terms of their emotions. The purpose of this study was to determine the frequency distribution of the incidence of postpartum blues in adolescent mothers in Ilir Barat II District, Palembang. The research design used non-experimental research methods with descriptive research methods. The study was conducted on 28 postpartum teenage mothers. Data collection using EPDS questionnaire in September 2023 to October 2023. The results showed that postpartum teenage mothers as many as 10 respondents (29.4%) had possible postpartum blues, 18 respondents (64.3%) had postpartum blues, 2 respondents (7.1%) had possible postpartum depression, and 1 respondent (3.6%) had postpartum depression. This study also examined the characteristics of the incidence of postpartum blues, namely age, parity, marital status, education level, occupation, and type of delivery in postpartum adolescent mothers. The results of this study are expected to prevent the occurrence of postpartum blues in adolescent mothers and provide information about the impact of early marriage that occurs in the community.